2015
DOI: 10.1111/ajco.12294
|View full text |Cite
|
Sign up to set email alerts
|

Impact of incidental findings on integrated 2-[18F]-fluoro-2-deoxy-D-glucose positron emission tomography/computed tomography in patients with gastric cancer

Abstract: Incidental findings on PET/CT were common. Although the incidental findings were suspicious of malignancy, most were benign with high costs for additional investigations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
2
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 17 publications
1
2
1
Order By: Relevance
“…Similar findings have been reported for cohorts with other primary cancer types (35,36), and the prevalence in our material is at a comparable level. The additional work-up generated by the findings is an important factor in evaluating the cost-effectiveness of 18 F-FDG PET/CT, since follow-up examinations are costly and often yield negative results.…”
Section: Discussionsupporting
confidence: 92%
“…Similar findings have been reported for cohorts with other primary cancer types (35,36), and the prevalence in our material is at a comparable level. The additional work-up generated by the findings is an important factor in evaluating the cost-effectiveness of 18 F-FDG PET/CT, since follow-up examinations are costly and often yield negative results.…”
Section: Discussionsupporting
confidence: 92%
“…There is limited literature from North America surrounding cost implications of follow-up investigations for IFs on PET/CT imaging. A Korean study reported a cost of USD$283.35 per IF based on South Korea's Health Insurance Review and Assessment Service reimbursement values, higher than that observed in our study potentially because of the high number of serologic and microbiologic tests that were performed as a result of IFs [20]. In our study, the average cost of follow-up investigations of CAD$105.51 (USD$127.56) based on all recommended investigations, and CAD$22.77 (USD$29.14) based on investigations actually performed, is in line with additional costs relating to IFs identified on conventional CT [4], suggesting that the PET component may not substantially increase costs of follow-up investigations for IFs.…”
Section: Discussioncontrasting
confidence: 77%
“…In contrast, Wang et al [17] investigated only hypermetabolic lesions, and found 199 of 1727 (12%) patients with an FDG-avid IF, whereas Agress and Cooper [11] found 53 of 1750 (3%) patients with at least 1 unexpected hypermetabolic focus; of the 42 cases available with histopathological diagnoses, 30 were malignant or premalignant. Including IFs identified on either the PET or CT components, as in our study, Chopra et al [19] reported 175 of 818 (21%) patients had at least 1 IF whereas Tae et al [20] found 386 of 421 (91.7%) patients with at least 1 IF. However, Chopra et al included only patients with lung cancer and Tae et al included only patients with gastric cancer.…”
Section: Discussionmentioning
confidence: 54%
“…Additionally, there is no consensus guideline on how to categorize PET‐CT findings; therefore, these results are heavily influenced by the individual study design. For example, one study focused on lung cancer reported an incidental finding rate of 21% while another study focused on gastric cancer reported an incidental finding rate of 91.7% 16,17 …”
Section: Discussionmentioning
confidence: 99%